الخلع شروطه وأثاره بين الشريعة الإسلامية وقانون الأسرة الجزائري (مجلة الواحات للبحوث والدراسات, 2020)
Islamic Legislation Was Found To Achieve Lofty Intentions, And The Basis Of These Intentions For Marital Relationship Is That The Spouses Live In An Atmosphere Of Affection, Mercy, Serenity And Cooperation. And Since It Was From The Nature Of The Human Soul, Which Is Not Upright In Any Case, A Dissension May Arise After The Affection That Eludes The Marital Ten With Him, Due To The Dislike Of One Of The Other, Which Leads To His Aversion To Him And His Inability To Continue Marital Life With Him, Because Of The Absence Of The Purpose Upon Which Marital Life Is Built From Housing And Affection, Mercy, And The Performance Of Mutual Duties Between Them Where This Life Becomes Irreparable, In This Case Islam Has Embarked On An Appropriate Remedy For It Which Is Separation, Either By Divorce, Divorce Or Dislocation. Key Words: Dislocation, Divorce, Breaking The Conjugal Bond, Redemption.